A new embolic liquid agent comprised of amino acid. Issue 1 (2nd January 2018) - Baba, Yasutaka; Higashi, Michiyo; Awai, Kazuo
Abstract: Transcatheter arterial or venous embolization has been widely used to address solid tumors by occluding the tumor-feeding vessels. It is also performed to treat portosystemic shunts and to stop bleeding by repair of the site of trauma. Commonly used embolic materials are gelatin sponges, coils, beads, and liquid agents such as absolute ethanol, histoacyryl, and onyx. In the field of interventional radiology, embolotherapy is performed routinely. Liquid embolization agents have different characteristics. Their coagulation time, the inflammatory reaction of the vascular wall or surrounding tissue, and their adhesion to the vascular wall vary. PuraMatrix, a liquid embolic agent not yet available for clinical use, is comprised of amino acid. We introduce and discuss preliminary experimental studies to examine its potential for use in humans.